The Role of Leadership Styles In Building and Sustaining Corporate Reputation – Empirical Investigation On Islamic Banks In Jordan - Tasneem F. Alfalah (International Review of Management and Marketing, 2017)
Leadership is the art and science of affecting the others; leaders in different organizational settings play a crucial role in achieving organizational goals, by establishing and offering motivational atmosphere for their employees. However, the main objective of this research is to build a theoretical model of leadership styles and corporate reputation in order to empirically within the context of Islamic banks operating in Jordan. The researcher used a quantitative methodological approach through a structured questionnaire to gather data from the research respondents. The sample size consisted of 640 employees from low-mid managerial levels. The researcher used descriptive statistics, multiple regression models and weighted least square analyses to examine the relationship between the research variables. Accordingly, the results revealed that both (transactional and transformational) leadership styles have a positive influence on corporate reputation. Meanwhile, transformational leadership style showed a positive and significant influence on corporate reputation. Also, privacy has a non-significant effect on mobile marketing acceptance but its effect is positive. Further, employee empowerment was found as mediator variable. Research conclusions, Limitations and recommendations for future work were also discussed.